(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article examines and analyzes the public opinion of the population on combating corruption. Public opinion plays an important role in the prevention and eradication of vices that hinder the development of society. The article analyzes the results of a sociological survey conducted in seven regions of the Republic. As you know, today in most states, various mechanisms for preventing corruption have been developed and implemented. Consequently, the analysis of the results of the conducted research was carried out by applying the results of this analysis to society. It is the above question that is considered in the article, which analyzes the results of a sociological study, which is an effective mechanism for eradicating corruption.